238 THE EFFECT OF INTUBATION ON TIME OF APPEARANCE OF POSITIVE RESPIRATORY CULTURES IN VERY LOW BIRTH WEIGHT INFANTS BETWEEN 450 AND 1250 GRAMS. (1st January 2005) - Chiang, C.; Hodgman, J. E.; Barton, L.
Abstract : Background: Previous studies have shown that assisted ventilation and respiratory infections lead to increased rates of chronic lung disease in very low birth weight (VLBW) infants. However, little is known about when respiratory infections are most likely to begin in ventilated VLBW infants. Objective: To evaluate when infectious organisms and what type appear in endotracheal tube aspirate cultures of ventilated infants weighing ≥450 grams and ≤1250 grams. Design and Methods: Retrospective chart review of 30 infants born at LAC+USC Women's and Children's Hospital between January 2002 and June 2004, weighing ≥450 grams and ≤1250 grams, who were intubated at birth, placed on assisted ventilation, and eventually discharged home or lived at least until day of life 30, were evaluated for respiratory culture results. Endotracheal tube aspirates of the infants were collected at birth and 3 times weekly for the duration of the intubation. Results were evaluated to determine when positive cultures were obtained and what types of organisms were present. Results: Fifty-five percent of the infants included in the review had positive respiratory cultures by day of life 10; all but 3 of these infants had negative respiratory cultures at birth. Those infants with positive respiratory cultures at birth had a period with negative cultures and then had positive cultures again by day of life 10. Sixty-five percent of the infants included in the review had positive respiratory cultures by day of life 11; of this group, 75% were delivered via cesarean section, 78% received a 7-day course of antibiotics, 85% received at least one dose of surfactant, and 64% had mothers who did not have prolonged rupture of membrane (PROM). No significant difference in rate of delivery type, PROM, or antibiotic course was found in infants with negative cultures by day 11 of life. Conclusions: The majority of intubated VLBW infants ≤1250 grams on assisted ventilation develop positive respiratory cultures by at least 11 days of age.